Crises and Disruption on Bali Tourism: Natural Disaster, Civil Unrest and Terrorism - Shantika, Budi; Bestari, Ni Made Prasiwi (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
This study investigates the significant impacts of various crises on the tourism industry in Bali, focusing on natural disasters, civil unrest, and terrorism. As a globally renowned destination, Bali's tourism sector is crucial to its economy, yet it faces substantial challenges that threaten its sustainability and cultural integrity. Through a systematic narrative review and bibliometric analysis, this research synthesizes existing literature to identify key crises that have historically influenced tourist arrivals and perceptions. Notably, events such as earthquakes, volcanic eruptions, and political instability have led to dramatic declines in visitor numbers and have instilled lasting psychological effects on potential travelers. For instance, the 2018 Lombok earthquake resulted in a 30% drop in tourist arrivals, highlighting the vulnerability of the tourism infrastructure. The findings underscore the urgent need for Bali to diversify its economic base, adopt sustainable tourism practices, and develop comprehensive crisis management strategies to enhance resilience against future disruptions. Additionally, the study reveals that while economic challenges are pronounced, cultural resilience has emerged, with local traditions adapting to maintain engagement through virtual platforms during crises. Recommendations for future research include exploring the evolving dynamics of tourism in Bali in the context of global challenges such as climate change and shifting tourist behaviors. By addressing these issues holistically, Bali can better safeguard its natural and cultural resources while continuing to thrive as a premier tourist destination. Keywords: Bali, tourism, natural disasters, civil unrest, crisis management, sustainability.